GENDER AND LANGUAGE ATTITUDES AMONG BANDUNG’S MILLENNIALS - Rosadi, Elda Mnemonica; Trianto, Ikmal (Ensiklopedia of Journal, 2025)
This study examines gender-based language attitudes toward the Sundanese language among millennial speakers in Bandung, focusing on three dimensions: language loyalty, language pride, and awareness of language norms. A mixed-method approach was employed, combining quantitative data from structured questionnaires with qualitative insights from open-ended interviews. The sample consisted of male and female millennials aged 28–40. Results indicate that both male (82.40%) and female (81.09%) respondents demonstrate strong positive attitudes toward language loyalty, particularly in acknowledging the importance of mastering and transmitting Sundanese. Language pride was also high among males (67%) and females (69.55%), although some respondents questioned the effectiveness of maintaining Sundanese in digital spaces. Awareness of language norms emerged as the most challenging dimension, with lower positive responses from females (41%) compared to males (59%). Female respondents often shifted to Indonesian to maintain politeness norms, while males cited fluency challenges and limited digital use. The findings suggest that sustaining Sundanese vitality requires strategies that address both affective and practical aspects of language use, incorporating gender-sensitive approaches, vocabulary and register mastery, and inclusive digital engagement.Keywords: language attitude, gender, Sundanese language, millenials, sociolinguistics